Synthesis of Molecularly Imprinted Polymers for the Extraction of p-Hydroxybenzoic Acid - Showkat Ahmad, Bhawani; AQIL FAIZ, MOHAMAD RAMEZAN,; Rachel Marcella, Roland; MOHAMAD AIMAN, OTHMAN; Aldrin Felix, Simbas (Asian Journal of Chemistry, 2025)
p-Hydroxybenzoic acid (p-HBA) is widely found in the environment due of its exceptional properties and has been used in the synthesis of variety of products such as preservatives, dyes, bactericides, etc. This causes a huge disposal of p-HBA in the environment which is considered to be harmful to both aquatic and terrestrial life. The molecular imprinting technique was employed to fabricate a molecularly imprinted polymer (MIP) that possesses selective binding sites for the p-HBA. In this study, p-HBA was used as the template molecule for the MIP synthesis, which was carried out using the precipitation polymerization method with a non-covalent approach. Acrylic acid was employed as the functional monomer, while ethylene glycol dimethylacrylate (EGDMA) was utilized as the cross-linker. The characterization of the MIP of p-HBA was conducted with scanning electron microscopy (SEM) and Fourier transform infrared (FTIR). The SEM results showed that both MIP and the non-imprinted polymer (NIP) of p-HBA were spherical in shape. The MIP attained its highest efficiency at optimum conditions of 1 ppm initial concentration, 0.4 g of polymer dosage and 210 min contact time. Moreover, the competitive binding assay indicated that the MIP displayed a greater affinity towards p-HBA than benzoic acid. The synthesized MIP was successfully used for the extraction p-HBA from blood serum and the extraction efficiency was about 80.56%.